Acute injury to the mouse carotid artery provokes a distinct healing response - Warwick, Timothy; Buchmann, Giulia Karolin; Pflüger-Müller, Beatrice; Spaeth, Manuela; Schürmann, Christoph; Abplanalp, Wesley; Tombor, Lukas; John, David; Weigert, Andreas; Leo-Hansmann, Martin; Dimmeler, Stefanie; Brandes, Ralf P. (Frontiers in Physiology, 2023)
Treatment of vascular stenosis with angioplasty results in acute vascular damage, which may lead to restenosis. Owing to the highly complex cellularity of blood vessels, the healing response following this damage is incompletely understood. To gain further insight into this process, scRNA-seq of mouse carotid tissue after wire injury was performed. Stages of acute inflammation, resolution and remodeling were recapitulated in these data. To identify cell types which give rise to neointima, analyses focused on smooth muscle cell and fibroblast populations, and included data integration with scRNA-seq data from myocardial infarction and atherosclerosis datasets. Following carotid injury, a subpopulation of smooth muscle cells which also arises during atherosclerosis and myocardial infarction was identified. So-called stem cell/endothelial cell/monocyte (SEM) cells are candidates for repopulating injured vessels, and were amongst the most proliferative cell clusters following wire-injury of the carotid artery. Importantly, SEM cells exhibit specific transcriptional profiles which could be therapeutically targeted. SEM cell gene expression patterns could also be detected in bulk RNA-sequencing of neointimal tissue isolated from injured carotid vessels by laser capture microdissection. These data indicate that phenotypic plasticity of smooth muscle cells is highly important to the progression of lumen loss following acute carotid injury. Interference with SEM cell formation could be an innovative approach to combat development of restenosis.